(untitled) (Bangladesh Medical Journal Khulna, 2014)
Cystic hygroma is a congenital malformation of the lymphatic system. Surgical excision is the treatment of choice, but injection of a sclerosing agent into the cyst is an alternative procedure. The aim of this study was to review the efficacy of intralesional bleomycin injection in cystic hygroma. This study was carried out in a private clinic in Khulna over a period of 2 years on 7 patients. Bleomycin at a dosage of 0.4-0.6 mg/kg was injected into the cyst and repeated injection was given at an interval of 4-8 weeks. Clinical outcomes were reviewed and analyzed. Seven patients, 4 males and 3 females, aged between one month and 4 years were treated with intralesional bleomycin injections. Complete clinical resolution was obtained in 6 cases (86%). Mass reduction was noted in 1 (14%) patient. Adverse reactions including mild fever, local swelling, redness and pain at the site of injection occurred in 3 cases (43%). These reactions persisted for only a few days. Transient systemic side effect like vomiting noted in one patient. So intralesional bleomycin injection is a safe and effective alternative to the surgical treatment of cystic hygroma. DOI: http://dx.doi.org/10.3329/bmjk.v46i1-2.18233 Bang Med J (Khulna) 2013; 46 : 12-15